Factors that interfer with adhesion to the treatment of Diabetes Mellitus type 2 (Research, Society and Development, 2022)
Objective: This study aimed to identify and define which factors interfere with adherence to type 2 Diabetes Mellitus (DM2) self-care activities. Methods: A hundred three (103) adults both sexes, diagnosed with Type 2 Diabetes Mellitus, have participated in this study. They were assessed through a socioeconomic questionnaire, Diabetes Self-Care Activities Questionnaire (DSCAQ) and International Physical Activity Questionnaire. (IPAQ). The study was carried out in the city of Três Corações-MG, from August 2018 to October 2019. Results: In the DSCA questionnaire, the activity with the highest adherence was related to medication intake (6,52 days ±1,52) and the lowest adherence was the activity related to the practice of specific physical exercises (1,29 days ±2,11). The IPAQ questionnaire determined that 66.0% of the participants reached the physical activity recommendations from the American Diabetes Association. By identifying the factors that interfere with adherence to self-care activities with DM2 and physical activity recommendation it was found through the cluster analysis Pearson's chi-square that the education low level (p